A Picomolar Transition State Analogue Inhibitor of MTAN as a Specific Antibiotic for Helicobacter pylori - Shanzhi Wang; Antti M. Haapalainen; Funing Yan; Quan Du; Peter C. Tyler; Gary B. Evans; Agnes Rinaldo-Matthis; Rosemary L. Brown; Gillian E. Norris; Steven C. Almo; Vern L. Schramm (2012)
Campylobacter and Helicobacter species express a 6-amino-6-deoxyfutalosine N-ribosylhydrolase (HpMTAN) proposed to function in menaquinone synthesis. BuT-DADMe-ImmA is a 36 pM transition state analogue of HpMTAN, and the crystal structure of the enzyme-inhibitor complex reveals the mechanism of inhibition. BuT-DADMe-ImmA has a MIC(90) value of <8 ng/mL for Helicobacter pylori growth but does not cause growth arrest in other common clinical pathogens, thus demonstrating potential as an H. pylori-specific antibiotic.